2013
DOI: 10.1002/eji.201343429
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeting of human DCSIGN drastically enhances CD8+T‐cell‐mediated protective immunity

Abstract: Vaccination is one of the oldest yet still most effective methods to prevent infectious diseases. However, eradication of intracellular pathogens and treatment of certain diseases like cancer requiring efficient cytotoxic immune responses remain a medical challenge. In mice, a successful approach to induce strong cytotoxic CD8 + T-cell (CTL) reactions is to target antigens to DCs using specific antibodies against surface receptors in combination with adjuvants. A major drawback for translating this strategy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…21 Importantly, delivery of antigens via anti-DC-SIGN monoclonal antibodies (aDC-SIGN) enhances T cell responses in vitro and in vivo. 18,19,22,23 An advantage of targeting antigens to CLRs is the possibility to modify antigens with the natural ligands of CLR, i.e., carbohydrates, which are small compared to antibodies. Glycans are naturally expressed throughout the body and therefore poorly immunogenic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Importantly, delivery of antigens via anti-DC-SIGN monoclonal antibodies (aDC-SIGN) enhances T cell responses in vitro and in vivo. 18,19,22,23 An advantage of targeting antigens to CLRs is the possibility to modify antigens with the natural ligands of CLR, i.e., carbohydrates, which are small compared to antibodies. Glycans are naturally expressed throughout the body and therefore poorly immunogenic.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] In addition, we showed that in combination with an adjuvant, DC-SIGN triggering modulates cytokine responses 26 and elicits strong CD4 C and CD8 C effector T cell responses in murine and human models. 23,26 However, whether targeting antigens to CLRs such as DC-SIGN using glycans yields superior tumor immunity than using specific antibodies is not known at present.…”
Section: Introductionmentioning
confidence: 99%
“…Although none of the DC immune markers has perfect sensitivity or specificity, DC-SIGN, which participates in T cell stimulation, [14][15][16][17] is considered reliable in distinguishing myeloid DCs from macrophages. 18,19 In kidney biopsies, DC-SIGN + cells stain with other known kidney DC markers (BDCA-1, 8 HLA-DR, 8 CD68, 7,8 and CX3CR1 10 ), show an activated but not fully mature DC phenotype, and are associated with high T cell stimulation capability.…”
mentioning
confidence: 99%
“…Targeting of dextran-binding receptors (e.g., MR and DC-SIGN) is a popular concept. In recent years studies devoted to the development of DC-SIGN therapeutic ligands have yielded new data in cell biology (203), immunology (204), and biochemistry (205, 206). The concept of therapeutic DC-SIGN antagonists/inhibitors is promising and in need of further development (9, 207).…”
Section: Discussionmentioning
confidence: 99%